Stage-by-Stage Inversion and Optimization Algorithm of Capacitor Parameters for Multistage Induction Coil Launcher - Su, Xiang; Lin, Fuchang; Zhang, Qin; Li, Hua; Liu, Yi (IEEE transactions on plasma science, 2022)
In this article, for a multistage induction coil launcher, the current loop model is established to solve its dynamic process. The McKinney analysis method is extended to the multistage situation. Also, the particle swarm optimization algorithm with linearly decreasing inertia weight (PSO-W) is introduced to optimize the trigger position of each driving coil. The voltage equation of the passive circuit is transformed into a standard first-order matrix differential equation, and then, the relationship between the induced current and the excitation current is solved. The expression shows that the armature resistance causes the reversal of the induced current and force. By equating the motion state of the armature with a time-varying resistance, a second-order circuit model with dynamic parameters is established. Based on the principle that the current waveform in the driving coil matches the motion state of the armature, the optimization algorithm of capacitor parameters is deduced. When the goal entry and exit speed of the armature are given, the capacitor parameters are inverted stage by stage. Finally, the above optimization algorithm is applied to a five-stage induction coil launcher. The field-circuit coupling simulation verifies the optimization results. The speed error is less than 2%, and the system has a high launch efficiency.